2008
DOI: 10.2137/145960607782219328
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of loin and ham quality in Finnish Landrace and Large White pigs

Abstract: Selection potential for meat quality of economically important loin (longissimus) and ham muscles (adductor, semimembranosus, biceps femoris) has been assessed. Ultimate pH (pH u ), meat colour (lightness, redness and yellowness), drip loss and two visually scored colour traits were recorded from 483 Finnish Landrace and 494 Finnish Large White station test pigs in a half-sib design. A univariate restricted maximum likelihood procedure was used to estimate variance components. The statistical model contained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Physicochemical properties of pork neck slices chill‐stored for 1, 4, and 7 days and frozen‐stored for 5 months are presented in Table . The results showed that pH, L* , a* , and b* values were in accordance with previous study (Sevon‐Aimonen, Honkavaara, Maki‐Tanila, & Puonti, ), showing that the dark meat was characterized by a high value of pH and color a* , low value of L* and b* when compared with light meat. The wide variation of pH, L* , a* , and b* values obtained in the current study were typical for dark muscles, as reported by Sevon‐Aimonen et al ().…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Physicochemical properties of pork neck slices chill‐stored for 1, 4, and 7 days and frozen‐stored for 5 months are presented in Table . The results showed that pH, L* , a* , and b* values were in accordance with previous study (Sevon‐Aimonen, Honkavaara, Maki‐Tanila, & Puonti, ), showing that the dark meat was characterized by a high value of pH and color a* , low value of L* and b* when compared with light meat. The wide variation of pH, L* , a* , and b* values obtained in the current study were typical for dark muscles, as reported by Sevon‐Aimonen et al ().…”
Section: Resultssupporting
confidence: 90%
“…Sevon-Aimonen, Honkavaara,Maki-Tanila, & Puonti, 2007), showing that the dark meat was characterized by a high value of pH and color a*, low value of L* and b* when compared with light meat. The wide variation of pH, L*, a*, and b* values obtained in the current study were typical for dark muscles, as reported bySevon-Aimonen et al (2007). Statistical analysis showed that there was no significant differences in pH, L*, a*, and b* between pork neck samples with different storage time (p > .05).…”
mentioning
confidence: 98%
“…The technological quality attributes of meat include: pH value, color, texture, water-holding capacity (WHC) and chemical composition (Rosenvold and Andersen 2003, Olsson and Pickova 2005, Sevón-Aimonen et al 2007. These parameters are influenced by multiple interacting factors including breed, genetics, feeding, pre-slaughter treatment and stunning, slaughter method, chilling and storage conditions, as reviewed by Rosenvold and Andersen (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of inferior muscle quality, especially with PSE and RSE defects, has an economic impact in the pork industry (Kauffman et al 1992, Joo et al 2000a, O'Neill et al 2003, Huff-Lonergan and Lonergan 2005, Sevón-Aimonen et al 2007. For this reason, evaluation of technological quality of pork represents an important step in meat production and processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation